2010
DOI: 10.3310/hta14020
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab, sorafenib tosylate, sunitinib and temsirolimus for renal cell carcinoma: a systematic review and economic evaluation

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 15 publications
2
78
0
Order By: Relevance
“…In essence, there only exist two studies of the cost-effectiveness of sunitinib, the company study PenTAG and the HTA study used for the NICE technology appraisal [11]. Estimates from the PenTAG model suggested that none of the interventions would be considered cost-effective at a willingness-to-pay threshold of 30,000 pounds per quality-adjusted life-year (QALY).…”
Section: Cost-effectiveness Studies Of New Therapies For Mrccmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, there only exist two studies of the cost-effectiveness of sunitinib, the company study PenTAG and the HTA study used for the NICE technology appraisal [11]. Estimates from the PenTAG model suggested that none of the interventions would be considered cost-effective at a willingness-to-pay threshold of 30,000 pounds per quality-adjusted life-year (QALY).…”
Section: Cost-effectiveness Studies Of New Therapies For Mrccmentioning
confidence: 99%
“…The cost of treatment with the new targeted therapies are in the range of UKP 3-6000 per 6 weeks, more than most patients can afford to pay. Decisions about their use in clinical practice would thus benefit from information about cost-effectiveness [11].…”
Section: Renal Cell Carcinoma and New Targeted Therapiesmentioning
confidence: 99%
“…In the sourced trials of sunitinib, SFN and BEV/ IFN, patient cohorts were similar with regard to the proportion of patients with clear cell histology, prior nephrectomy, gender distribution and MSKCC risk groups. The In keeping with epidemiological data indicating that <1% of patients with mRCC survive for 10 years [18,35], the present model assumed a 10-year time horizon to represent a lifetime perspective [23]. Accordingly, PFS and OS data were extrapolated to 10 years using patientlevel data and parametric survival curves.…”
Section: Discussionmentioning
confidence: 99%
“…A National Institute for Health and Clinical Excellence (NICE) Health Technology Assessment estimate of the cost effectiveness of treatments for mRCC stated that sunitinib was likely to be considered cost effective above a WTP threshold of £75,000 per QALY gained compared with both BEV/IFN and IFN-. Subsequently, NICE recommended the use of sunitinib as fi rst-line treatment for patients with advanced mRCC with an Eastern Cooperative Oncology Group performance status of 0 or 1 and considered suitable for immunotherapy [16,18]. Similarly, in another cost-effectiveness analysis based on indirect comparisons using the Markov economic model adapted for the Swedish Health Service, sunitinib was seen as a cost-effective option for fi rst-line mRCC therapy compared with SFN, BEV/IFN and temsirolimus [40].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation